Aspek Yuridis Pemberian Remisi Terhadap Narapidana Di Masa Pandemi COVID-19 - Nadine Yemersa Imanuela Alfons; Deassy Jacomina Anthoneta Hehanussa; Lionie Lokollo (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The policy of releasing prisoners in an effort to suppress the spread of COVID-19 is the authority of the Indonesian government through the Ministry of Law and Human Rights.Purposes of the Research: To find out the implementation of granting remissions during the COVID-19 pandemic and to find out the factors that hinder the implementation of granting remissions for prisoners during the COVID-19 pandemic.Methods of the Research: This study uses empirical juridical research with the legal materials used in the study are primary and secondary data in the form of interviews with correctional officers.Results of the Research: This study uses empirical juridical research with the legal materials used in the study are primary and secondary data in the form of interviews with correctional officers, Law Number 12 of 1995 concerning Corrections, Presidential Decree Number 174 of 1999 concerning Remission, Government Regulation Number 99 of 2012 concerning the Second Amendment to Government Regulation Number 32 of 1999 concerning Terms and Procedures for the Implementation of the Rights of Prisoners, Law Number 8 of 1981 concerning Criminal Procedure Code.